Evaluation Of Urban Park Design Criteria: In The Case Of Taraqi Park (Afghanistan, Herat) - Yücel, Gökçen Firdevs (UXUC - User Experience and Urban Creativity, 2020)
The objective of this study is to define park design standards, determine the user expectations of the parks and evaluate the defined standards in the case of Taraqi Park in Herat city. On-site detection, observation and survey methods were utilized in the study. The conformity of the park area with international standards was evaluated while general satisfaction as to the park was tried to be determined by virtue of surveys made with the users of the park.